O papel do psicólogo organizacional na gestão de empresas familiares - Kaipper, Raissa de Amaral (My University, 2023)
The theme of this work addresses the role of the organizational psychologist in business management relatives. The general objective of the present study was to identify the responsibilities of the psychologist organization in the development of strategic level managers in family businesses. The specific objectives were to characterize organizational structures; characterize company family and its management; describe the development of strategic managers and describe the duties of the organizational psychologist. The method was designed as a research exploratory, in order to obtain better knowledge and improvement about the practice of organizational psychology in this context of action. The sources used for this research these were scientific articles made available in the Scopus database. 34 were found articles that contained the key words, where 6 of them were relevant to the theme of the present study. The analysis framework used was content analysis (Laville, & Dionne 1999). As results it was identified that family businesses make up a part importance of large business groups, a fact that guarantees them a place of importance in the world economy, and makes it pertinent to carry out studies that seek to deepen the characteristics relating to its dynamics. These companies, even though they have the most varied forms, have a central characteristic, which is the fact that they have their origin and history linked to a family where members are in charge of managing the business having expectations regarding their continuity in the organization. Organizational psychology It will be important for developing strategy through people management. Through these processes, it will be possible to plan interventions aligned with organizational policies in order to bring the expected improvements and development that managers need. The psychologist organization has a fundamental role to play within these organizations in order to enhance their strengths and ensure that they remain and grow more and more in the market. [resumo fornecido pelo autor]
O tema do presente trabalho aborda o papel do psicólogo organizacional na gestão de empresas familiares. O objetivo geral do presente estudo foi identificar as atribuições do psicólogo organizacional no desenvolvimento de gestores de nível estratégico nas empresas familiares. Os objetivos específicos foram caracterizar estruturas organizacionais; caracterizar empresa familiar e sua gestão; descrever desenvolvimento de gestores estratégicos e descrever as atribuições do psicólogo organizacional. O método teve como delineamento uma pesquisa exploratória, a fim de obter melhor conhecimento e aprimoramento sobre a prática da psicologia organizacional nesse contexto de atuação. As fontes utilizadas para essa pesquisa foram artigos científicos disponibilizados na base de dados Scopus. Foram encontrados 34 artigos que continham as palavras chaves, onde 6 deles tinham relevância com o tema do presente estudo. O referencial de análise utilizado foi análise de conteúdo (Laville, & Dionne 1999). Como resultados foi identificado que as empresas familiares compõem uma parte importante dos grandes grupos empresariais, fato esse que lhes garante um lugar de importância na economia mundial, e torna pertinente a realização de estudos que buscam aprofundar as características referentes a sua dinâmica. Essas empresas, mesmo apresentando as mais variadas formas, dispõem de uma característica central, que é o fato de possuírem a sua origem e história ligadas a uma família onde os membros estão à frente da administração dos negócios tendo, expectativas a respeito de sua continuidade na organização. A psicologia organizacional será importante para a elaboração de estratégia por meio da gestão de pessoas. Através desses processos será possível planejar intervenções alinhadas com as políticas organizacionais a fim de trazer as melhorias esperadas e o desenvolvimento que os gestores precisam. O psicólogo organizacional tem um papel fundamental a desempenhar dentro dessas organizações, a fim de potencializar suas forças e fazer com que se mantenham e cresçam cada vez mais no mercado. [resumo fornecido pelo autor]
Keywords: Psicologia; Empresas familiares; Psicologia organizacional